Boundary Tension at the Interface of Nanoscopic Helium Films on an Heterogeneous Substrate - Hernandez, Ester Susana (2014)
This paper reports the first calculation of the two-dimensional interfacial profile and energetics of nanoscopically thin films of helium, on an heterogeneous planar substrate consisting of two adjoining metals. The calculations are performed in the frame of density functional theory at zero temperature, with the purpose of identifying the formation process of the interface at the boundary between the two substrates when few atomic layers are involved, to elucidate the possible relationship of the magnitude of the boundary tension with the displacement of layers between the half films, and to extract keys to organize future calculations of film coexistence at finite temperatures.